2019
DOI: 10.1242/bio.040519
|View full text |Cite
|
Sign up to set email alerts
|

Dietary iron restriction leads to a reduction in hepatic fibrosis in a rat model of non-alcoholic steatohepatitis

Abstract: Iron overload in the liver causes oxidative stress and inflammation, which result in organ dysfunction, making it a risk factor for non-alcoholic steatohepatitis (NASH) and hepatocellular carcinoma. We aimed to evaluate the effect of dietary iron restriction on disease progression in rats fed a choline-deficient L-amino acid-defined (CDAA) diet. Male F344 rats were fed a choline-sufficient amino acid-defined (control) diet, a CDAA diet or an iron-restricted CDAA diet for 4, 8 and 12 weeks. At each time point, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 29 publications
(44 reference statements)
2
15
0
Order By: Relevance
“…In addition, the systemic inflammatory state induced by NAFLD may predispose the organism to increased hepcidin levels. Serum iron levels previously reported in rats fed with the MCD diet, were comparable with those found in the MCD rats used in this study [39]. Furthermore, no significant increase in serum iron documented in the present study was comparable with results previously reported: significantly higher levels in serum iron occurred only after 4 weeks [39].…”
Section: Iron and Nafldsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, the systemic inflammatory state induced by NAFLD may predispose the organism to increased hepcidin levels. Serum iron levels previously reported in rats fed with the MCD diet, were comparable with those found in the MCD rats used in this study [39]. Furthermore, no significant increase in serum iron documented in the present study was comparable with results previously reported: significantly higher levels in serum iron occurred only after 4 weeks [39].…”
Section: Iron and Nafldsupporting
confidence: 92%
“…Serum iron levels previously reported in rats fed with the MCD diet, were comparable with those found in the MCD rats used in this study [39]. Furthermore, no significant increase in serum iron documented in the present study was comparable with results previously reported: significantly higher levels in serum iron occurred only after 4 weeks [39]. The lack in serum Fe alterations may be attributed to early NAFLD stage; this result could also explain the absence of significant correlations versus pro-inflammatory markers.…”
Section: Iron and Nafldsupporting
confidence: 90%
“…The choline-deficient L-amino acid defined (CDAA) diet is similar to the MCDD, with a low quantity of methionine (0.1%) and an average caloric density of 4320 kcal/kg. This diet, administered to Fisher 344 or Wistar rats for 6–12 weeks, induced severe steatosis with inflammation but lacked ballooning phenotypes [ 39 , 40 ]. Animals were not overweight compared to the control group and did not develop metabolic syndrome.…”
Section: Diet-induced Nafld and Nash Models In Ratsmentioning
confidence: 99%
“…Multiple murine models of NAFLD/NASH have been developed using obesogenic or nutrient-de cient diets, chemical induction, genetic modi cation, or a combination of these manipulations [11][12][13][14][15][16][17]. MS-NASH mouse, formerly published as FATZO [18], was developed by crossing C57Bl/6 and AKR/J strains with selection for dysmetabolic phenotypes.…”
Section: Introductionmentioning
confidence: 99%